Drivers and dynamic mechanisms of sports tourism integration in cross-border regions: Evidence from the Guangdong-Hong Kong-Macao Greater Bay Area - Jun Yuan; Canyu Chen; Zhouxin Luo; Yanhong Liu (PLoS ONE, 2026)
The integration of sports tourism industry plays a crucial role in fostering high-quality regional economic growth, enhancing industrial coordination, improving quality of life and promoting sustainable tourism development, particularly in cross-border regions. However, existing research has predominantly focused on macro-level policy and market analyses, paying limited attention to micro-level drivers and underlying mechanisms. To address this gap, this study adopts a mixed-methods approach, using the Guangdong-Hong Kong-Macao Greater Bay Area (GBA) as a case study. Grounded Theory is first employed to identify key drivers and construct a conceptual model of their dynamic mechanisms. Subsequently, Structural Equation Modeling (SEM) is applied to empirically test the model. The results confirm six significant drivers that positively influencing integration outcomes: government behavior, resource environment, enterprise development, market demand, technological innovation, and human capital. Notably, the analysis reveals substantial differences in their impact strength. Human capital (β = 0.619, p < 0.001) and technological innovation (β = 0.541, p < 0.001) emerge as the dominant drivers, followed by enterprise development needs (β = 0.321, p < 0.001). In contrast, market demand (β = 0.065, p < 0.001), resource environment (β = 0.041, p = 0.017), and government behavior (β = 0.052, p = 0.002) show the weakest direct effects, with government behavior further constrained by policy fragmentation. To facilitate high-quality and sustainable integration, targeted policy recommendations are proposed, including enhancing cross-border policy coordination and institutional alignment, leveraging technological innovation through digital integration platforms, strengthening enterprise-led collaboration and cross-border industrial clusters, cultivating and mobilizing interdisciplinary talent across the region, and expanding segmented markets through differentiated regional branding. This study contributes to the theoretical framework of sports tourism integration by empirically elucidating the interplay and relative strength of the drivers and their dynamic mechanisms in cross-border contexts. Furthermore, it offers actionable insights for policymakers and industry stakeholders in the GBA.